Monitoring system of agricultural performance based on multisensor data and cross‐validation technique in merging temporal images. (28th September 2022) - Bhavani, N. P. G.; Chillakuru, Prameeladevi; Adusumilli, Ramana Lakshmi; Alroobaea, Roobaea; Rubaiee, Saeed; S. Hanbazazah, Abdulkader; Mann, Suman
Abstract: Several approaches to forecasting agricultural production have been used across the country, but they have focused on information widely detected with technology that was not very successful. Unfortunately, because of many difficulties such as climate variables (50% global fog cover) with limited temporal accuracy, the remotely detected information necessary to predict crop production was often insufficient. As a result of these problems, existing methods of estimating agricultural production are ineffective or out of date. Several efforts have been made to overcome these challenges by combining images with high temporal accuracy but poor geographic detail. On the other hand, it is this kind of situation that is most suitable for extremely large and homogeneous agricultural areas. An innovative theoretical framework has developed that explains this absence of high‐quality satellite images. This intelligent method was built around this new theoretical framework, which incorporates its use of something like the energy equation to improve the predictions of multiple cultures. Many producers were contacted and data regarding agricultural production were obtained to validate the results of the smart technology. The excellent reliability of this intelligent method has been shown by a comparative contrast between projected crop yields and actual output in various areas. Core Ideas: Methods of forecasting agricultural production are ineffective or out of date. An innovative theoretical framework has been developed. Data regarding agricultural production were obtained to validate results of smart technology.